Analysis of Factors Affecting Consumer's Decision in Choosing the Digital Fund Wallet - Heny Herawati (Britain International for Academic Research (BIAR-Publisher), 2021)
This study aims to determine the effect of price, reference groups, and security on consumer decisions in choosing digital fund wallets on three campuses in Jakarta. This study used a sample of 100 respondents and the sampling technique used a simple random sampling technique. The data collection technique used a questionnaire of 43 question items which were assessed on a Likert scale of 1-5 and tested for validity and reliability. The analytical method use, regression analysis, correlation, the test of the coefficient of determination (R2), and t-test. Based on the regression analysis at a significant level of 5%, it shows (1) there is a positive and significant effect of price on consumer decisions in choosing a digital fund wallet, with a rx1y correlation of 0.678; the coefficient of determination R2x1y of 0.460; and sig value 0.000 < 0.05; (2) there is a positive and significant influence of the reference group on consumer decisions in choosing a digital fund wallet, with a rx2y correlation of 0.607; the coefficient of determination R2x2y is 0.368; and sig value 0.000 <0.05; (3) there is a positive and significant security effect on consumer decisions in choosing a digital fund wallet, with a rx3y correlation of 0.746; the coefficient of determination R2x3y of 0.556; and sig value 0.000 < 0.05.